Implication of livelihood diversification on wetland resources conservation: A case from Bangladesh - Rahman, Md. Mijanur; Begum, Anwara (Journal of Wetlands Ecology, 2011)
The Management of Aquatic Ecosystems through Community Husbandry was demonstrated in Hail Haor from 1999 to 2008 to ensure sustainable wetland resources management and conservation. This paper focused the importance of diversified livelihood options for the resources users to increase income, diversify income sources and improve the wetland productivity. A long-term support to 2,004 resources users was provided to explore income generation schemes through skills and credit. Income generation activities were adopted in 15 different types of trades that covered poultry and livestock rearing, fish culture, operating small business, tailoring or establishing tree nursery. These offered greater income and stability for the resources users. The overall income gained by the resources users around 64% where income generation activities contributed 50% of the total income they gained in 2006. Fishing effort was reduced almost 43% and over 14% fishers left fishing. New livelihoods helped them moving into other occupations reducing dependency on wetland resources that enabled habitat and fish stock recovery. Exploring diversified livelihoods could help the resources users to involve in wetland resources restoration process without livelihood deprivation. Key words: Resources user; livelihood option; fishing effort; wetland restoration; resources conservation DOI: http://dx.doi.org/10.3126/jowe.v5i0.4905 J Wet Eco 2011 (5): 59-65